Superior elimination of Cr(VI) using polydopamine functionalized attapulgite supported nZVI composite: Behavior and mechanism. (January 2022) - Ma, Bo; Yao, Jun; Chen, Zhihui; Liu, Bang; Kim, Jonghyok; Zhao, Chenchen; Zhu, Xiaozhe; Mihucz, Victor G.; Minkina, Tatiana; Knudsen, Tatjana Šolević
Abstract: In this study, a polydopamine (PDA) modified attapulgite (ATP) supported nano sized zero-valent iron (nZVI) composite (PDA/ATP-nZVI) was rapidly synthesized under acidic conditions, and employed to alleviate Cr(VI) toxicity from an aqueous solution. Kinetic studies revealed that Cr(VI) adsorption process followed the pseudo-second order model, suggesting chemisorption was the dominant adsorption mechanism. Liu isotherm adsorption model was able to better describe the Cr(VI) adsorption isotherm with the maximum adsorption capacity of 134.05 mg/g. The thermodynamic study demonstrated that the adsorption process occurred spontaneously, accompanied by the increase in entropy and endothermic reaction. Low concentrations of coexisting ions had negligible effects on the removal of Cr(VI), while high concentrations of interfering ions were able to facilitate the removal of Cr(VI). Reactive species test revealed that Fe 2+ played a key role in Cr(VI) reduction by PDA/ATP-nZVI. PDA enhanced the elimination of Cr(VI) via donation of electrons to Cr(VI) and acceleration of Fe 3+ transformation to Fe 2+ . Furthermore, PDA was able to effectively inhibit the leaching of iron species and generation of ferric hydroxide sludge. Mechanistic study revealed that 72% of Cr(VI) elimination was attributed to reduction/precipitation, while 28% of Cr(VI) elimination was due to the surface adsorption. Graphical abstract: Image 1 Highlights: The PDA/ATP-nZVI composite was rapidly synthesized under acidic condition. PDA/ATP-nZVI exhibited a remarkable adsorption capacity for Cr(VI). High concentrations of coexisting ions enhanced the removal of Cr(VI). PDA accelerated conversion of Fe 3+ to Fe 2+, leading to enhanced reduction of Cr(VI). 28% of Cr(VI) removal was due to adsorption, and 72% was ascribed to reduction.